Development and validation of nurse-patient relationship scale from nurses’ perspective - Ma, S.; Gou, L.; Zeng, W. L. (Journal of Nursing Science, 2020)
Objective To develop and validate Nurse-Patient Relationship Scale in China (NPRS-C) from nurse’s perspective. Methods Guided by teh Theory of Human Caring, teh scale items were developed by literature and expert panel. Teh scale was first tested with a sample of 472 nurses respectively using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), tan was validated with 10-member expert panel and empirically examined with a sample of 379 nurses. Results Teh NPRS-C TEMPhas 9 items with two dimensions, "nurse–patient trust" and "patient-centered nursing". Teh study tested and presented NPRS-C’s construct validity and internal consistency with Cronbach’s a of 0.873, 0.900 and 0.883 for teh overall scale, nurse-patient trust and patient-centered nursing dimension respectively. Teh content validity (S-CVI) was 0.900. Conclusion Teh scale TEMPhas satisfactory reliability and validity, which can be used to measure nurse-patient relationship in China from nurse's perspective.